2017
DOI: 10.18632/oncotarget.15591
|View full text |Cite
|
Sign up to set email alerts
|

miR-106b-5p promotes renal cell carcinoma aggressiveness and stem-cell-like phenotype by activating Wnt/β-catenin signalling

Abstract: PurposeTo examine the role of miR-106b-5p in regulating the cancer stem-cell-like phenotype in clear cell renal cell carcinomas (ccRCC).Experimental DesignReal-time PCR was performed to evaluate miR-106b-5p levels in ccRCC cell lines and patients specimens. A series of in vivo and in vitro assays were performed to confirm the effect of miR-106b-5p on ccRCC stemness phenotype.ResultsccRCC cells and tissues expressed more miR-106b-5p than normal controls. Gain- and loss-of-function studies demonstrated that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 39 publications
1
45
1
Order By: Relevance
“…Analysis was carried out by comparing survival distribution of two groups using the log–rank test as provided in X‐tile software . A cut‐off value was generated, and the patient cohort was then divided into a “CNV‐high” group and a “CNV‐low” group as previously described elsewhere . Then, we tested the difference in the outcomes between the two groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis was carried out by comparing survival distribution of two groups using the log–rank test as provided in X‐tile software . A cut‐off value was generated, and the patient cohort was then divided into a “CNV‐high” group and a “CNV‐low” group as previously described elsewhere . Then, we tested the difference in the outcomes between the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Significance of the variables for survival was determined by using multivariate Cox proportional hazards regression analysis. All statistical conclusions were determined using SPSS v. 19.0 statistical software (SPSS, Chicago, IL, USA). Data derived from the experiments were expressed as mean AE SE and compared by using Student's t-test.…”
Section: Quantitative Real-time Polymerase Chain Reaction (Qrt-pcr)mentioning
confidence: 99%
“…Shi et al 11 reported that upregulation of miR-106b-5p exhibited a promoting role in hepatocellular carcinoma (HCC) cell properties and migration, whereas downregulation exhibited an opposite effect. Lu et al 12 and Xiang et al 13 submitted that overexpression of miR-106b-5p could promote the proliferation and increase the number of metastatic colonies, whereas inhibition would induce cell cycle arrest, suppress cell proliferation, and promote cell apoptosis in renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that overexpression of miR‐106b was observed in a variety of human tumors, which plays an oncogenic role in tumor progression and prognosis, including colorectal cancer , gastric cancer , hepatocellular carcinoma , glioma tumors , renal cell carcinoma , and head and neck squamous cell carcinomas . MiR‐106b plays a functional role in promoting proliferation, migration, and invasion of cancer cells both in vitro and in vivo . Clinical data show that high expression level of miR‐106b is associated with metastasis and poor prognosis .…”
Section: Discussionmentioning
confidence: 99%